Aberrant Type I Interferon Regulation in Autoimmunity: Opposite Directions in MS and SLE, Shaped by Evolution and Body Ecology - Reder, Anthony T.; Feng, Xuan (Frontiers in Immunology, 2013)
Studying the action of mechanisms of type I IFN provides the insight to elucidate the cause and therapy for autoimmune diseases. There are high IFN responses in some diseases such as connective tissue diseases, but low responses in multiple sclerosis. Distinct IFN features lead us to understand pathology of a spectrum of autoimmune diseases and help us to search genetic changes, gene expression, and biomarkers for diagnosis, disease progression, and treatment response.